2012
DOI: 10.1042/cs20120239
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species enhance AMP-activated protein kinase activation in the endothelium of patients with coronary artery disease and diabetes

Abstract: The aim of the present study was to determine whether the endothelial dysfunction associated with CAD (coronary artery disease) and T2D (Type 2 diabetes mellitus) is concomitant with elevated mtROS (mitochondrial reactive oxygen species) production in the endothelium and establish if this, in turn, regulates the activity of endothelial AMPK (AMP-activated protein kinase). We investigated endothelial function, mtROS production and AMPK activation in saphenous veins from patients with advanced CAD. Endothelium-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 41 publications
(71 reference statements)
0
48
0
2
Order By: Relevance
“…AMPK can be induced by glucose deprivation and mitochondrial O 2 − production (Wu and Wei, 2012) (Mackenzie et al, 2013) to reduce total ROS via the promotion of pentose phosphate shunt-mediated NADPH production (Jeon et al, 2012). Consistent with these studies, Hif-1α −/− MEFs that stably expressed HIGD1A increased pAMPK levels to a greater extent than control cells during glucose deprivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK can be induced by glucose deprivation and mitochondrial O 2 − production (Wu and Wei, 2012) (Mackenzie et al, 2013) to reduce total ROS via the promotion of pentose phosphate shunt-mediated NADPH production (Jeon et al, 2012). Consistent with these studies, Hif-1α −/− MEFs that stably expressed HIGD1A increased pAMPK levels to a greater extent than control cells during glucose deprivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial hormesis was initially used to describe the beneficial acute increase in mitochondrial respiration when cells are exposed to toxins such as heavy metals (94). A beneficial role of mitochondrial superoxide may be linked to improved endothelial function because 2-DOG was found to stimulate AMPK and phosphorylate eNOS via stimulation of ROS (95). Exercise has been shown to stimulate muscle ROS production, and a study in humans found that exercise increased adiponectin levels and insulin sensitivity; however, pretreatment with antioxidants (vitamin C and vitamin E) led to a loss of the protective benefits of exercise (96).…”
Section: New Theory Of Mitochondrial Hormesis As a Central Player In mentioning
confidence: 99%
“…Kukidome and co-workers have demonstrated that metformin could prevent diabetes complications by multiple mechanisms, for instance, decreasing blood glucose level, reducing ROS production through AMPK activation and/or PGC-1␣ induction and promotes mitochondrial biogenesis in HUVEC cells [150]. It has also been shown that ROS enhances AMPK activation in the endothelium of patients with coronary artery disease and diabetes [151]. This finding may implicate high glucose levels in the induction of endothelial dysfunction by increasing ROS production, which in turn leads to the activation of AMPK [144].…”
Section: Er Stress and Pathogenesis Of Diabetes Complicationsmentioning
confidence: 97%